(untitled) (Agroindustrial Science, 2026)
Food production is a fundamental pillar of global food systems, and vertical farming (VF) has emerged as a promising strategy to address food security challenges in urban areas. This review synthesizes evidence on VF through a systematic analysis of scientific and technical literature retrieved from Google Scholar and ScienceDirect, following the PRISMA 2020 Flow Diagram methodology. The conceptual structure of the field was examined using a term co-occurrence network analysis with VOSviewer (2025). The selected studies were classified according to the environmental, economic, and social dimensions of sustainability, with emphasis on water use efficiency and energy consumption, technical and economic feasibility, and food security, respectively. The findings indicate that VF is receiving increasing global attention due to its potential to enhance urban resilience and its growing acceptance among producers and consumers. However, VF remains an emerging technology, and further research is required to improve its feasibility, particularly through reducing environmental impacts, optimizing energy efficiency, and strengthening economic performance. Strategic investments in renewable energy, smart agriculture, and water-efficient technologies will be essential to ensure the long-term sustainability and scalability of VF in urban food systems.